Cohabitation With a Known Coronavirus Disease 2019 Case Is Associated With Greater Antibody Concentration and Symptom Severity in a Community-Based Sample of Seropositive Adults. (24th July 2021) - Schrock, Joshua M; Ryan, Daniel T; Saber, Rana; Benbow, Nanette; Vaught, Lauren A; Reiser, Nina; Velez, Matthew P; Hsieh, Ryan; Newcomb, Michael; Demonbreun, Alexis R; Mustanski, Brian; McNally, Elizabeth M; et al.
Abstract: In a community-based sample of seropositive adults (n = 1101), we found that seropositive individuals who lived with a known coronavirus disease 2019 (COVID-19) case exhibited higher blood anti–severe acute respiratory syndrome coronavirus 2 spike receptor-binding domain immunoglobulin G concentrations and greater symptom severity compared to seropositive individuals who did not live with a known COVID-19 case. Abstract : Exposure intensity may contribute to severity of SARS-CoV-2 infection. Seropositive participants who had lived with a known COVID-19 case had higher antibody concentrations and greater symptom severity compared to seropositive participants who had not lived with a known COVID-19 case.